1986
DOI: 10.1128/mcb.6.9.3086
|View full text |Cite
|
Sign up to set email alerts
|

Simian virus 40 DNA replication: functional organization of regulatory elements.

Abstract: The efficiency of simian virus 40 (SV40) DNA replication is dependent on the structural organization of the regulatory region. The enhancing effect of the G+C-rich 21-base-pair (bp) repeats on SV40 DNA replication is position and dose dependent and to some extent orientation dependent. The inverted orientation is about 50% as effective as the normal orientation of the 21-bp repeat region. Movement of the 21-bp The double-stranded circular genome of simian virus 40 (SV40) represents a simple model system for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
65
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 43 publications
9
65
0
Order By: Relevance
“…On the other hand, a highly replication-efficient, enhancerless plasmid such as p2x210ri given in trans at the same level as the test plasmid effectively inhibits the enhancer-containing test plasmids. Such a competition for replication between two plasmids which is decided in favor of the more efficiently replicating plasmid has been observed previously by other workers (46,47).…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…On the other hand, a highly replication-efficient, enhancerless plasmid such as p2x210ri given in trans at the same level as the test plasmid effectively inhibits the enhancer-containing test plasmids. Such a competition for replication between two plasmids which is decided in favor of the more efficiently replicating plasmid has been observed previously by other workers (46,47).…”
Section: Resultssupporting
confidence: 50%
“…However, even from a distance of 5 kb from the promoter, the 72-bp enhancer can activate transcription by at least 10-fold over that obtained without the enhancer (71). On the other hand, the replication activation property of the SV40 72-bp repeat (which is exhibited only in the absence of the intervening 21-bp repeat [14,36,46,47]) is highly position dependent; replication is activated at 8 to 9 bp from the SV40 core origin, but not at 99 bp or more (11). A similar finding has also been made for the polyomavirus system (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SV40 enhancer was one of the first enhancers to exhibit strong activity. It is composed of a 72 bp repeated sequence without obvious partiality in race and can exert a 2-to 20-fold enhancement of gene transcription in different host cells (18,19). Previous results have shown that the transcription activity of human telomerase reverse transcriptase (hTERT) promoter was significantly enhanced after it was modified using SV40 enhancer (20).…”
Section: Discussionmentioning
confidence: 99%